Pharmacy practice in Pakistan - Hussain, Azhar; Jamshed, Shazia Qasim (Elsevier Inc., 2016)
The healthcare system of Pakistan is very well-designed, with the public sector catering to the health of the masses and the private sector functioning in parallel with a commercial viewpoint. A total of 76% of health expenditures in Pakistan are out-of-pocket payment. A total of 405 pharmaceutical units were registered in Pakistan, of which 31 were multinational. The number of registered pharmaceutical units topped 4400, which could be in the best interest of consumers due to the initiation of the price competition phenomenon. The distribution of medicines relies heavily on community pharmacies. The pharmacy education sector has not contributed significantly to the national healthcare system of Pakistan. In 2004, pharmacy education was upgraded to a 5-year PharmD program, but an inadequate number of experienced and qualified staff, mainly in the area of pharmacy practice, is still a major challenge. There is a dire need to create awareness regarding the role of pharmacists in the community, most likely by utilizing mass media campaigns.